PENGARUH BERPIKIR KRITIS TERHADAP HASIL BELAJAR MATEMATIKA - Resti Saputri; Nintin Nurlela; Yuyun Elizabeth Patras (Universitas Pakuan, 2020)
THE EFFECT OF CRITICAL THINKING ON MATHEMATICS LEARNING OUTCOMESThis research was conducted using an associative quantitative research approach with a type of causal approach consisting of two variables namely critical thinking as an independent variable and mathematics learning outcomes as the dependent variable. The main objective of this research is to find out the positive influence between critical thinking and mathematics learning outcomes. The subjects of this study were students of class IV-A. IV-B, and IV-C. Bogor City Pondok Rumput Elementary School consisting of 49 respondents. The research was carried out in the first semester of the 2019/2020 school year. The instrument validity test uses the Person Product Moment correlation formula and the reliability test uses the Cronbach Alpha formula. Test data analysis requirements using the test for normality, homogeneity, and linearity. The average value on the critical thinking variable was 109.7 and the average value on the mathematics learning variable was 68.1. Then the results of the study showed that there was an influence of critical thinking on mathematics learning outcomes, indicated by statistical analysis that produced a path coefficient (pxy) value of 0.64. This shows the influence of critical thinking on mathematics learning outcomes, while the coefficient of determination (r2) of 0.409 or 40.9%. This means the value of the influence of critical thinking on mathematics learning outcomes of 40.9%, through the regression equation The remaining 59.1% is determined by other factors. Based on the results of the research above, it can be concluded that there is a positive influence between critical thinking on students' mathematics learning outcomes. This means that one of the factors in mathematics learning outcomes is due to students' critical thinking at the time of learning.